Leukemogenic Ptpn11 allele causes defective erythropoiesis in mice. - Tatiana Usenko; Gordon Chan; Emina Torlakovic; Ursula Klingmüller; Benjamin G Neel (PLoS ONE, 2014)
Src homology 2 (SH2) domain-containing phosphatase 2 (SHP2), encoded by PTPN11, regulates signaling networks and cell fate in many tissues. Expression of oncogenic PTPN11 in the hematopoietic compartment causes myeloproliferative neoplasm (MPN) in humans and mice. However, the stage-specific effect(s) of mutant Ptpn11 on erythroid development have remained unknown. We found that expression of an activated, leukemogenic Ptpn11 allele, Ptpn11D61Y, specifically in the erythroid lineage causes dyserythropoiesis in mice. Ptpn11D61Y progenitors produce excess cKIT+ CD71+ Ter119- cells and aberrant numbers of cKITl° CD71+ erythroblasts. Mutant erythroblasts show elevated activation of ERK, AKT and STAT3 in response to EPO stimulation, and MEK inhibitor treatment blocks Ptpn11D61Y-evoked erythroid hyperproliferation in vitro. Thus, the expression of oncogenic Ptpn11 causes dyserythropoiesis in a cell-autonomous manner in vivo.